2020
DOI: 10.1038/s41467-020-15666-2
|View full text |Cite
|
Sign up to set email alerts
|

Escape mutations circumvent a tradeoff between resistance to a beta-lactam and resistance to a beta-lactamase inhibitor

Abstract: Beta-lactamase inhibitors are increasingly used to counteract antibiotic resistance mediated by beta-lactamase enzymes. These inhibitors compete with the beta-lactam antibiotic for the same binding site on the beta-lactamase, thus generating an evolutionary tradeoff: mutations that increase the enzyme's beta-lactamase activity tend to increase also its susceptibility to the inhibitor. Here, we investigate how common and accessible are mutants that escape this adaptive tradeoff. Screening a deep mutant library … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…For instance, Jahn et al demonstrated that variations in treatment dynamics can significantly alter evolved resistance for some antibiotics, such as tetracycline, but not others, such as amikacin and piperacillin ( 18 ). Other evolution experiments that were systematically conducted using a range of concentrations for β-lactams ( 19 ) and erythromycin ( 20 ) have highlighted the concentration-dependent adaptability of Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jahn et al demonstrated that variations in treatment dynamics can significantly alter evolved resistance for some antibiotics, such as tetracycline, but not others, such as amikacin and piperacillin ( 18 ). Other evolution experiments that were systematically conducted using a range of concentrations for β-lactams ( 19 ) and erythromycin ( 20 ) have highlighted the concentration-dependent adaptability of Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%
“…These mutants are also likely to confer resistance to REL, NAC, and ZID. However, resistance to AVI can also arise from mutations to the Ω-loop and the H-10 helix (16,(44)(45)(46). Figure 3A).…”
Section: Structural Basis Of Ampc Ec Inhibition By Dbosmentioning
confidence: 99%
“…Aztreonam (ATM) is stable to the hydrolysis of MBLs ( 10 , 11 ), and the combination of aztreonam-avibactam (ATM-AVI) has activity against CPE producing serine-based carbapenemases, MBLs, or both and has the potential to be a major option for combatting CPE. Unfortunately, ATM-AVI-resistant strains have been found ( 12 14 ), but the resistance mechanisms remain poorly studied. In this study, we report a unique combination of ATM-AVI resistance mechanisms in Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%